Modernisasi Administraasi Perpajakan dalam Rangka Optimalisasi Pelayanan Pajak Berbasis Digital - Redo Alpha Hernando; Dian Wahyudin (Jurnal Pajak Vokasi (JUPASI), 2020)
In a tax policy, the measure of success lies in the tax administration itself. To provide optimal services to the community, tax reform is needed in the form of modernizing tax administration. The purpose of the modernization of tax administration is to increase tax compliance, increase public trust (trust), and increase the integrity of the tax apparatus. This study aims to provide an overview of how the modernization of tax administration can improve tax services and the ease that can be felt by taxpayers in complying with tax obligations and improve the integrity of tax officials in the management of the tax. The method used in this writing is descriptive qualitative, where the approach used is the study of literature. The results of this paper are an increase in state revenue from the tax sector, increased compliance and more optimal tax services by modernizing digital-based tax administration